CFD Modeling of Crossflow Membrane Filtration- Integration of Filtration Model and Fluid Transport Model - Khor, E.; Kumar, Perumal; Samyudia, Yudi (CUTSE 2009, 2009)
Cross-flow membrane filtration has become a promising technique for waste-water treatment as compared to conventional treatment methods. One of the reasons is that the membrane techniques offer separation that can be achieved at ambient temperature with minimum energy. It is also an innovation for the application of cross-flow filtration in oil and gas industry especially as an integral part for the oil-in-water analysis of produced water prior to offshore disposal. However, good fouling control is essential for the efficiency of the cross-flow filtration unit. With the fact that membrane is not a passive entity, the understanding of particle deposition phenomena is vital for reducing fouling. In this paper, filtration will be modeled through the relationship between hydrodynamics of the cross-flows and the transfer of flows across the membrane. The results of FLUENT simulated model are in good agreement with experimental results. Simulation results of the model are presented and then validated using experimental data for distilled (DI) water. From the model, some connecting variables are identified and established in this modeling work. By attaining these connections, optimization of membrane filtration can be achieved by adjusting the operating parameters.